Галина Уланова - Львов-Анохин Борис Александрович (Искусство, 1984)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 14575 / Цена: 4.90 / Сис.шифр: 85.335.423 / Авт.знак: Л 89 / ГРНТИ: 18 / ББК: 85.335.423